Adverse airway events in parturient compared with non-parturient patients. Is there a difference? Results from a quality management project - Heinrich, Stefan; Irouschek, Andrea; Prottengeier, Johannes; Ackermann, Andreas; Schmidt, Joachim (Journal of Obstetrics and Gynaecology Research, 2015)
The fear of airway problems often leads to prolonged attempts to obtain neuroaxial (spinal anesthesia or epidural anesthesia) anesthesia in obstetric anesthesia. The aim of this institutional quality management study was to revisit existing anesthesia care in the obstetric department, focusing on the frequency of delayed or failed neuroaxial anesthesia as well as the risk of airway problems in parturient and non-obstetric patients.The clinical records from 8 consecutive years (2005-2013) were analyzed retrospectively. Cases of cesarean delivery with general anesthesia were analyzed and compared with an age-matched group of female patients undergoing non-obstetric abdominal or gynecological surgery with rapid sequence induction. Poor laryngeal visualization (Cormack-Lehane grade III or IV) and failed intubation were recorded.The records of 6393 cesarean deliveries including 851 with general anesthesia were analyzed. In 175 cases insufficient or delayed onset of regional anesthesia led to requirement for general anesthesia. The rate of poor laryngoscopic view in parturient women undergoing cesarean delivery was 14/851, and 4/814 in the reference group (P = 0.023). Failed intubation occurred in three patients undergoing cesarean delivery (0.4%) and in one non-obstetric patient (0.1%; P = 0.339).The rate of failed intubations in patients undergoing cesarean delivery may be equivalent to non-obstetric patients. In time-challenging cesarean deliveries, delay of conversion from non-successful neuroaxial anesthesia to general anesthesia in order to avoid adverse airway events does not appear to be justified.
EVALuna2:16690

Comparison of clinical outcome variables in patients with and without etomidate-facilitated anesthesia induction ahead of major cardiac surgery: a retrospective analysis - Heinrich, Stefan; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Harig, Frank; Castellanos, Ixchel (Critical Care, 2014)
It is well known that etomidate may cause adrenal insufficiency. However, the clinical relevance of adrenal suppression after a single dose of etomidate remains vague. The aim of this study was to investigate the association between the administration of a single dose of etomidate or an alternative induction regime ahead of major cardiac surgery and clinical outcome parameters associated with adrenal suppression and onset of sepsis.The anesthesia and intensive care unit (ICU) records from patients undergoing cardiac surgery over five consecutive years (2008 to 2012) were retrospectively analyzed. The focus of the analysis was on clinical parameters like mortality, ventilation hours, renal failure, and sepsis-linked serum parameters. Multivariate analysis and Cox regression were applied to derive the results.In total, 3,054 patient records were analyzed. A group of 1,775 (58%) patients received a single dose of etomidate; 1,279 (42%) patients did not receive etomidate at any time. There was no difference in distribution of age, American Society of Anesthesiologists physical score, duration of surgery, and Acute Physiology and Chronic Health Evaluation II score. Postoperative data showed no significant differences between the two groups in regard to mortality (6.8% versus 6.4%), mean of mechanical ventilation hours (21.2 versus 19.7), days in the ICU (2.6 versus 2.5), hospital days (18.7 versus 17.4), sepsis-associated parameters, Sequential Organ Failure Assessment score, and incidence of renal failure. Administration of etomidate showed no significant influence (P = 0.6) on hospital mortality in the multivariate Cox analysis.This study found no evidence for differences in key clinical outcome parameters based on anesthesia induction with or without administration of a single dose of etomidate. In consequence, etomidate might remain an acceptable option for single-dose anesthesia induction.
EVALuna2:16090

Comparison of Metal and Plastic Disposable Laryngoscope Blade with Reusable Macintosh Blade in Difficult and Inhalation Injury Airway Scenario: A Manikin Study - Moritz, Andreas; Heinrich, Stefan; Irouschek, Andrea; Birkholz, Torsten; Prottengeier, Johannes; Schmidt, Joachim (Journal of Emergency Medicine, 2017)
Single-use plastic blades (SUPB) and single-use metal blades (SUMB) for direct laryngoscopy and tracheal intubation have not yet been compared with reusable metal blades (RUMB) in difficult airway scenarios.The purpose of our manikin study was to compare the effectiveness of these different laryngoscope blades in a difficult airway scenario, as well as in a difficult airway scenario with simulated severe inhalation injury.Thirty anesthetists performed tracheal intubation (TI) with each of the three laryngoscope blades in the two scenario manikins.In the inhalation injury scenario, SUPB were associated with prolonged intubation times when compared with the metal blades. In the inhalation injury scenario, both metal laryngoscope blades provided a quicker, easier, and safer TI. In the difficult airway scenario, intubation times were significantly prolonged in the SUPB group in comparison to the RUMB group, but there were no significant differences between the SUPB and the SUMB. In this scenario, the RUMB demonstrated the shortest intubation times and seems to be the most effective device.Generally, results are in line with previous studies showing significant disadvantages of SUPB in both manikin scenarios. Therefore, metal blades might be beneficial, especially in the airway management of patients with inhalation injury.
EVALuna2:16733

Incidence and predictors of difficult laryngoscopy in 11,219 pediatric anesthesia procedures - Heinrich, Stefan; Birkholz, Torsten; Ihmsen, Harald; Irouschek, Andrea; Ackermann, Andreas; Schmidt, Joachim (Pediatric Anesthesia, 2012)
Difficult laryngoscopy in pediatric patients undergoing anesthesia.This retrospective analysis was conducted to investigate incidence and predictors of difficult laryngoscopy in a large cohort of pediatric patients receiving general anesthesia with endotracheal intubation.Young age and craniofacial dysmorphy are predictors for the difficult pediatric airway and difficult laryngoscopy. For difficult laryngoscopy, other general predictors are not yet described.Retrospectively, from a 5-year period, data from 11.219 general anesthesia procedures in pediatric patients with endotracheal intubation using age-adapted Macintosh blades in a single center (university hospital) were analyzed statistically.The overall incidence of difficult laryngoscopy [Cormack and Lehane (CML) grade III and IV] was 1.35%. In patients younger than 1 year, the incidence of CML III or IV was significantly higher than in the older patients (4.7% vs 0.7%). ASA Physical Status III and IV, a higher Mallampati Score (III and IV) and a low BMI were all associated (P < 0.05) with difficult laryngoscopy. Patients undergoing oromaxillofacial surgery and cardiac surgery showed a significantly higher rate of CML III/IV findings.The general incidence of difficult laryngoscopy in pediatric anesthesia is lower than in adults. Our results show that the risk of difficult laryngoscopy is much higher in patients below 1 year of age, in underweight patients and in ASA III and IV patients. The underlying disease might also contribute to the risk. If the Mallampati score could be obtained, prediction of difficult laryngoscopy seems to be reliable. Our data support the existing recommendations for a specialized anesthesiological team to provide safe anesthesia for infants and neonates.
EVALuna2:16625

Increased Rate of Poor Laryngoscopic Views in Patients Scheduled for Cardiac Surgery Versus Patients Scheduled for General Surgery: A Propensity Score-Based Analysis of 21,561 Cases - Heinrich, Stefan; Ackermann, Andreas; Prottengeier, Johannes; Castellanos, Ixchel; Schmidt, Joachim; Schüttler, Jürgen (Journal of Cardiothoracic and Vascular Anesthesia, 2015)
Former analyses reported an increased rate of poor direct laryngoscopy view in cardiac surgery patients; however, these findings frequently could be attributed to confounding patient characteristics. In most of the reported cardiac surgery cohorts, the rate of well-known risk factors for poor direct laryngoscopy view such as male sex, obesity, or older age, were increased compared with the control groups. Especially in the ongoing debate on anesthesia staff qualification for cardiac interventions outside the operating room a detailed and stratified risk analysis seems necessary.Retrospective, anonymous, propensity score-based, matched-pair analysis.Single-center study in a university hospital.No active participants. Retrospective, anonymous chart analysis.The anesthesia records of patients undergoing cardiac surgery in a period of 6 consecutive years were analyzed retrospectively. The results were compared with those of a control group of patients who underwent general surgery. Poor laryngoscopic view was defined as Cormack and Lehane classification grade 3 or 4.The records of 21,561 general anesthesia procedures were reviewed for the study. The incidence of poor direct laryngoscopic views in patients scheduled for cardiac surgery was significantly increased compared with those of the general surgery cohort (7% v 4.2%). Using propensity score-based matched-pair analysis, equal subgroups were generated of each surgical department, with 2,946 patients showing identical demographic characteristics. After stratifying for demographic characteristics, the rate of poor direct laryngoscopy view remained statistically significantly higher in the cardiac surgery group (7.5% v 5.7%).Even with stratification for demographic risk factors, cardiac surgery patients showed a significantly higher rate of poor direct laryngoscopic view compared with general surgery patients. These results should be taken into account for human resource management and distribution of difficult airway equipment, especially when cardiac interventional programs are implemented in remote hospital locations.
EVALuna2:16681

Sedation assessment in a mobile intensive care unit: a prospective pilot-study on the relation of clinical sedation scales and the bispectral index - Prottengeier, Johannes; Moritz, Andreas; Heinrich, Stefan; Gall, Christine; Schmidt, Joachim (Critical Care, 2014)
The critically-ill undergoing inter-hospital transfers commonly receive sedatives in continuation of their therapeutic regime or to facilitate a safe transfer shielded from external stressors. While sedation assessment is well established in critical care in general, there is only little data available relating to the special conditions during patient transport and their effect on patient sedation levels. The aim of this prospective study was to investigate the feasibility and relationship of clinical sedation assessment (Richmond Agitation-Sedation Scale (RASS)) and objective physiological monitoring (bispectral index (BIS)) during patient transfers in our Mobile-ICU.The levels of sedation of 30 pharmacologically sedated patients were evaluated at 12 to 17 distinct measurement points spread strategically over the course of a transfer by use of the RASS and BIS. To investigate the relation between the RASS and the BIS, Spearman's squared rank correlation coefficient (?(2)) and the Kendall's rank correlation coefficient (?) were calculated. The diagnostic value of the BIS with respect to the RASS was investigated by its sensitivity and positive predictive value for possible patient awakening. Therefore, measurements were dichotomized considering a clinically sensible threshold of 80 for BIS-values and classifying RASS values being nonnegative.Spearman's rank correlation resulted to ?(2) = 0.431 (confidence interval (CI) = 0.341 to 0.513). The Kendall's correlation coefficient was calculated as ? = 0.522 (CI = 0.459 to 0.576). Awakening of patients (RASS >= 0) was detected by a BIS value of 80 and above with a sensitivity of 0.97 (CI = 0.89 to 1.00) and a positive predictive value of 0.59 (CI = 0.45 to 0.71).Our study demonstrates that the BIS-Monitor can be used for the assessment of sedation levels in the intricate environment of a Mobile-ICU, especially when well-established clinical scores as the RASS are impracticable. The use of BIS is highly sensitive in the detection of unwanted awakening of patients during transfers.
EVALuna2:5483

Short- and long term effects of epidural analgesia on morbidity and mortality of esophageal cancer surgery - Heinrich, Stefan; Janitz, Katrin; Merkel, Susanne; Klein, Peter; Schmidt, Joachim (Langenbecks Archives of Surgery, 2015)
Perioperative regional anesthesia with consecutive reduction of intra- and postoperative systemic opioid requirements in order to improve oncological result after cancer surgery has only been addressed by a few reports. This hypothesis has never been proved in esophageal cancer with a long-term follow-up of more than 5 years. Therefore, we addressed the impact on short- and long-term outcomes of epidural analgesia for esophagus cancer surgery.All available records from patients who underwent esophageal cancer surgery from 1995 to 2005 were retrospectively analyzed. Short- and long-term outcome variables including opioid requirements, duration of ICU-stay, survival, and cancer recurrence were compared between patients with and patients without epidural analgesia for abdomino-right-thoracic esophagectomy.Overall, the analysis included 153 patients, 118 received epidural analgesia; in 35 patients, epidural analgesia was avoided. We found significantly increased postoperative median opioid consumption (10-day intravenous morphine equivalent 187 versus 104 mg) and duration of ICU hospitalization (10.1 vs. 5.9 days, p < 0.05) in the non-epidural group compared with the epidural group. However, there were no significant differences in cancer recurrence (23 % non-epidural group, 27 % epidural group), 1-year mortality (14 vs. 11 %), or 5-year survival (29 vs. 28 %) between the two patient groups.The results of our study underline the well-known clinical benefits of epidural analgesia for esophagus surgery. However, we found no evidence that the further oncological outcome is determined or significantly influenced by the presence or absence of epidural analgesia.
EVALuna2:15179

The prehospital intravenous access assessment: a prospective study on intravenous access failure and access delay in prehospital emergency medicine - Prottengeier, Johannes; Albermann, Matthias; Heinrich, Stefan; Birkholz, Torsten; Gall, Christine; Schmidt, Joachim (European Journal of Emergency Medicine, 2016)
Intravenous access in prehospital emergency care allows for early administration of medication and extended measures such as anaesthesia. Cannulation may, however, be difficult, and failure and resulting delay in treatment and transport may have negative effects on the patient. Therefore, our study aims to perform a concise assessment of the difficulties of prehospital venous cannulation.We analysed 23 candidate predictor variables on peripheral venous cannulations in terms of cannulation failure and exceedance of a 2 min time threshold. Multivariate logistic regression models were fitted for variables of predictive value (P<0.25) and evaluated by the area under the curve (AUC>0.6) of their respective receiver operating characteristic curve.A total of 762 intravenous cannulations were enroled. In all, 22% of punctures failed on the first attempt and 13% of punctures exceeded 2 min. Model selection yielded a three-factor model (vein visibility without tourniquet, vein palpability with tourniquet and insufficient ambient lighting) of fair accuracy for the prediction of puncture failure (AUC=0.76) and a structurally congruent model of four factors (failure model factors plus vein visibility with tourniquet) for the exceedance of the 2 min threshold (AUC=0.80).Our study offers a simple assessment to identify cases of difficult intravenous access in prehospital emergency care. Of the numerous factors subjectively perceived as possibly exerting influences on cannulation, only the universal - not exclusive to emergency care - factors of lighting, vein visibility and palpability proved to be valid predictors of cannulation failure and exceedance of a 2 min threshold.
EVALuna2:5542